Tidal disruption events from massive black hole binaries: predictions for ongoing and future surveys. Issue 3 (17th June 2019) - Thorp, Stephen; Chadwick, Eli; Sesana, Alberto
ABSTRACT: We compute the expected cosmic rates of tidal disruption events (TDEs) induced by individual massive black holes (MBHs) and by MBH binaries (MBHBs) – with a specific focus on the latter class – to explore the potential of TDEs to probe the cosmic population of sub-pc MBHBs. Rates are computed by combining MBH and MBHB population models derived from large cosmological simulations with estimates of the induced TDE rates for each class of objects. We construct empirical TDE spectra that fit a large number of observations in the optical, UV, and X-ray and consider their observability by current and future survey instruments. Consistent with results in the literature, and depending on the detailed assumption of the model, we find that LSST and Gaia in optical and eROSITA in X-ray will observe a total of 3000–6000, 80–180, and 600–900 TDEs per year, respectively. Depending on the survey, 1 to several per cent of these are prompted by MBHBs. In particular, both LSST and eROSITA are expected to see 150–450 MBHB-induced TDEs in their respective mission lifetimes, including 5–100 repeated flares. The latter provide an observational sample of binary candidates with relatively low contamination and have the potential of unveiling the sub-pc population of MBHBs in the mass range $10^5\lt M\lt 10^7\, M_\odot$, thus informing future low-frequency gravitational wave observatories.